Analisis Kebutuhan Pengembangan Media Ular Tangga Berbasis Etnomatematika Rumah Adat Bali Pada Materi Geometri dan Pengukuran Siswa Kelas V SD - Gusti Ketut Dewi Srimartini; I Putu Suardipa; I Komang Wahyu Wiguna (Jayapangus Press, 2026)
This study aimed to analyze the need for developing a snakes and ladders learning media based on the ethnomathematics of Balinese traditional houses in mathematics learning, particularly on geometry and measurement topics for fifth-grade elementary school students. The study employed a quantitative descriptive approach as part of the define stage of the 4D development model. The participants consisted of one classroom teacher and 20 fifth-grade students. Data were collected through observations and needs assessment questionnaires administered to both teachers and students and were analyzed descriptively using percentage techniques. The findings revealed that mathematics learning media were still limited to textbooks, worksheets, and simple instructional aids, while some students continued to experience difficulties in understanding geometry concepts. Both teachers and students expressed the need for more interactive, engaging, and contextual learning media. Furthermore, positive responses were shown toward the development of snakes and ladders learning media based on the ethnomathematics of Balinese traditional houses, as it was considered capable of integrating mathematics learning with local cultural values. These findings indicate that such learning media have the potential to be developed as an alternative mathematics learning resource that is appropriate for the characteristics of elementary school students.